Aspek Biologi Ikan Kepar (Belontia hasselti Valenciennes, 1831) - Indah Puspita Sari; Khairul Khairul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the biological aspects of twill fish in the swamp waters of PTPN Ajamu III. The method used is exploratory and the determination of the sampling point is done by purposive sampling. Fish samples were caught using fishing rods. All fish caught were measured for total length and weight. The results showed that for the small size class interval (9-11.9 cm) 11 males and 14 females were obtained; medium size class (12-14.9 cm) for 5 individual male fish and 19 individual female fish; and the large size class (15-17.9 cm) found only females with a total of 2 individuals. The relationship between length and weight of twill is negative allometric because of the value of the constant b > 3. The sex ratio of fish for males and females obtained is 1: 2. In conclusion, the population of twill fish is categorized as still maintained. Keywords: Biological Aspect, Belontia hasselti, Swamp Waters